ADVERSITY QUOTIENT DI KALANGAN MAHASISWA SEKOLAH TINGGI TEOLOGI KRISTUS ALFA OMEGA SEMARANG TAHUN AJARAN 2018/2019 - Christian Ezra Yulianto (JOURNAL of THEOLOGICAL STUDENTS, 2019)
Everyone has the ability to endure in him to stay in the face of pressure. When someone does not develop these abilities in him, then when facing difficulties the person will feel afraid, feel unable to solve the problem.  But when a person has the ability to survive when faced with pressure on him, it can be said that the person has a good adversity quotient in him.  Therefore, this research was conducted to measure the extent of the level of adversity quotient that students have at the Theological College of Christ Alfa Omega Semarang. This research is a study with one variable, with the number of respondents 91 students, that is 40 number of male students and 51 number of female students who actively study from odd semester 2018 to even semester 2019. This study uses samples. The researcher validated for 91 questionnaires using SPSS 17.0 and found that there were still invalid statement items from 64 items to 54 items.  Then the researchers managed all the collected data as many as 91 respondents with 54 items validated. After the authors conducted research in the field, the results obtained stated that the level of adversity quotient among students of the College of Christ theology in Alfa Omega Semarang was based on the calculation of the sample obtained 81.13%.